Picasso's war the destruction of Guernica and the masterpiece that changed the world - Martin, Russell 1952-; Picasso, Pablo 1881-1973. (New York, New York Dutton, a member of Penguin Putnam Inc., 2002)
On April 26, 1937, the Basque town of Guernica in northern Spain was bombed by Hitler's Luftwaffe in the midst of a bloody civil war on behalf of Francisco Franco's rebel forces. Twenty-four hours later, the village lay in ruins, its population decimated. This act of terror and unspeakable cruelty--the first large-scale attack against civilians in modern warfare-outraged the world, and one man in particular. Pablo Picasso, an expatriate living in Paris, responded to the devastation in his homeland by beginning work on Guernica, a painting that many today consider the greatest artwork of the twentieth century.

Weaving themes of politics, art, war, and morality, and featuring some of the twentieth century's most memorable and infamous figures, Martin follows this renowned masterwork across decades and continents. From Europe to America and, finally, back to Spain, Picasso's War sheds light on the conflict that was an ominous prelude to World War II and delivers an unforgettable portrait of a genius whose visionary statement about the horror and terrible wounds of war still resonates today. --Publisher description.
The Spanish Dead -- Remembering the Bullring -- Images Spilling from Fingers -- Save Spain! -- A Wearable Pair of Boots -- Exiles -- The Last Refugee -- Guernica in Gernika.
Includes bibliographical references (pages 271-272)
Keywords: Picasso, Pablo -- 1881-1973; Picasso, Pablo -- 1881-1973. -- Criticism and interpretation; Spain -- History -- Civil War, 1936-1939 -- Art and the war